Biphasic alterations in coronary smooth muscle Ca(2+) regulation in a repeat cross-sectional study of coronary artery disease severity in metabolic syndrome - McKenney-Drake, Mikaela L. (Atherosclerosis, 2016)
BACKGROUND AND AIMS: Coronary artery disease (CAD) is progressive, classified by stages of severity. Alterations in Ca(2+) regulation within coronary smooth muscle (CSM) cells in metabolic syndrome (MetS) have been observed, but there is a lack of data in relatively early (mild) and late (severe) stages of CAD. The current study examined alterations in CSM Ca(2+) regulation at several time points during CAD progression. METHODS: MetS was induced by feeding an excess calorie atherogenic diet for 6, 9, or 12 months and compared to age-matched lean controls. CAD was measured with intravascular ultrasound (IVUS). Intracellular Ca(2+) was assessed with fura-2. RESULTS: IVUS revealed that the extent of atherosclerotic CAD correlated with the duration on atherogenic diet. Fura-2 imaging of intracellular Ca(2+) in CSM cells revealed heightened Ca(2+) signaling at 9 months on diet, compared to 6 and 12 months, and to age-matched lean controls. Isolated coronary artery rings from swine fed for 9 months followed the same pattern, developing greater tension to depolarization, compared to 6 and 12 months (6 months= 1.8±0.6 g, 9 months= 5.0±1.0 g, 12 months= 0.7±0.1 g). CSM in severe atherosclerotic plaques showed dampened Ca(2+) regulation and decreased proliferation compared to CSM from the wall. CONCLUSIONS: These CSM Ca(2+) regulation data from several time points in CAD progression and severity help to resolve the controversy regarding up- vs. down-regulation of CSM Ca(2+) regulation in previous reports. These data are consistent with the hypothesis that alterations in sarcoplasmic reticulum Ca(2+) contribute to progression of atherosclerotic CAD in MetS.